The labour digital divide: digital dimensions of labour market segmentation. (1st January 2020) - Calderón-Gómez, Daniel; Casas-Mas, Belén; Urraco-Solanilla, Mariano; Revilla, Juan Carlos
Abstract : This paper investigates digitalisation in labour activities within the Spanish population, with the aim of examining its extent and characteristics in relation to the digital divide at work, focusing particularly on access to and use of the internet. It thus aims to analyse the digital dimension of job segregation in the Spanish labour market. Internet use is explored both as an indicator of the type of work carried out and, in aggregate terms, of the broader characteristics of the labour market. The authors argue that a new segmentation of the labour market might be emerging, based on the technological requirements of jobs. The article draws on data from a representative Spanish population survey on how employees access and use the internet at work. Univariate, bivariate and multivariate statistical analyses were performed to describe the correlation between digitalised labour practices and individual sociodemographic conditions. The results show that around a third of Spanish workers are not required to use the internet at work. This population falls into two categories: the 'analogical precariat', in poor socio-economic conditions; and 'traditional analogical labour', in better quality traditional jobs. Digital workers can be classified into three groups: the 'digital precariat' (with a poor economic situation); 'traditional digital labour' (mainly involved in productive digital tasks); and the 'innovative class' (carrying out productive and communicative digital tasks). The level of education is by far the most important determining variable, in relation both to general and advanced uses. Young people and women are prominent in less complex uses of the internet (the digital precariat), which are usually related to less qualified jobs. The article argues that this represents a more subtle gender discrimination in the digital sphere than in the analogue one, with women being overrepresented in the digital precariat and underrepresented in the innovative class, while also being overrepresented in traditional analogical labour.